Zinc finger gene nolz1 regulates the formation of retinal progenitor cells and suppresses the Lim3/Lhx3 phenotype of retinal bipolar cells in chicken retina. Issue 4 (20th December 2017) - Blixt, Maria K.E.; Konjusha, Dardan; Ring, Henrik; Hallböök, Finn
Abstract : Background : The zinc‐finger transcription factor Nolz1 regulates spinal cord neuron development by interacting with the transcription factors Isl1, Lim1, and Lim3, which are also important for photoreceptors, horizontal and bipolar cells during retinal development. We, therefore, studied Nolz1 during retinal development.Results: Nolz1 expression was seen in two waves during development: one early (peak at embryonic day 3–4.5) in retinal progenitors and one late (embryonic day 8) in newly differentiated cells in the inner nuclear layer. Overexpression and knockdown showed that Nolz1 decreases proliferation and stimulates cell cycle withdrawal in retinal progenitors with effects on the generation of retinal ganglion cells, photoreceptors, and horizontal cells without triggering apoptosis. Overexpression of Nolz1 gave more p27 positive cells. Sustained overexpression of Nolz1 in the retina gave fewer Lim3/Lhx3 bipolar cells.Conclusions: We conclude that Nolz1 has multiple functions during development and suggest a mechanism in which Nolz1 initially regulates the proliferation state of the retinal progenitor cells and then acts as a repressor that suppresses the Lim3/Lhx3 bipolar cell phenotype at the time of bipolar cell differentiation. Developmental Dynamics 247:630–641, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Nolz1 is expressed during two phases of retinal development: early in retinal progenitors and late in newly differentiated cells. Nolz1 decreases proliferation and stimulates cell cycle withdrawal in retinal progenitors. Nolz1 represses the Lim3/Lhx3 neuronal phenotype in bipolar cells.